Analisis Dampak Pandemi Covid-19 Terhadap Pendapatan Pengusaha Mebel JeparaA - Siti Fatimatuzzahroh (SENTRALISASI, 2023)
The impact of Covid-19 on the economy has a broad impact throughout Indonesia, the economy of each region is threatened coupled with worse regional conditions than before. This research examines the impact of Covid-19 on the income of Jepara furniture entrepreneurs with variable X capital, labor and raw materials and variable Y is income. This research uses quantitative methods. The sample in this study were 88 respondents representing furniture entrepreneurs in Jepara. The results showed that the variables of capital and raw materials had a positive and significant effect on the income of Jepara furniture entrepreneurs. Whereas the Labor variable has no significant positive effect on the income of Jepara furniture entrepreneurs.